The nitrogen cycle in anaerobic methanotrophic mats of the Black Sea is linked to sulfate reduction and biomass decomposition. Issue 2 (1st July 2013) - Siegert, Michael; Taubert, Martin; Seifert, Jana; von, Martin; Basen, Mirko; Bastida, Felipe; Gehre, Matthias; Richnow, Hans‐Hermann; Krüger, Martin
Abstract Anaerobic methanotrophic (ANME) mats host methane‐oxidizing archaea and sulfate‐reducing prokaryotes. Little is known about the nitrogen cycle in these communities. Here, we link the anaerobic oxidation of methane (AOM) to the nitrogen cycle in microbial mats of the Black Sea by using stable isotope probing. We used four different 15N‐labeled sources of nitrogen: dinitrogen, nitrate, nitrite and ammonium. We estimated the nitrogen incorporation rates into the total biomass and the methyl coenzyme M reductase (MCR). Dinitrogen played an insignificant role as nitrogen source. Assimilatory and dissimilatory nitrate reduction occurred. High rates of nitrate reduction to dinitrogen were stimulated by methane and sulfate, suggesting that oxidation of reduced sulfur compounds such as sulfides was necessary for AOM with nitrate as electron acceptor. Nitrate reduction to dinitrogen occurred also in the absence of methane as electron donor but at six times slower rates. Dissimilatory nitrate reduction to ammonium was independent of AOM. Ammonium was used for biomass synthesis under all conditions. The pivotal enzyme in AOM coupled to sulfate reduction, MCR, was synthesized from nitrate and ammonium. Results show that AOM coupled to sulfate reduction along with biomass decomposition drive the nitrogen cycle in the ANME mats of the Black Sea and that MCR enzymes are involved in this process.